Stings Of Pedophilia : Case Studies From Malaysia - Parveen Kaur, Sarjeet Singh; Hanis Khuraisyah, Karim; Arif, Jawaid; Sivashunmugam, Sangaran; Than Myint, Khin; Eshvin Raj, Singh; Muhammad, Rashid (Webology Center, 2022)
Pedophilia is a current topic in Malaysia since the imprisonment of Richard Huckle. This study was carried out due to the recent awareness among Malaysians regarding pedophilia issues. The main objectives of this study were to investigate the causes of pedophilia, effects on the victims, the effective treatments available in preventing pedophilic disorders and on the traumatized victims. This study was conducted by using qualitative method, i.e. through indepth interviews and observations at Hospital Permai, a psychiatric hospital, a few other places of the victims in Johor and Rumah Kanak-Kanak Toh Puan Hajah Norkiah, Kuching (abused children’s home). This study managed to interview three pedophiles, seven victims, a counsellor and a psychologist. The findings of the study show that the predators admit to have an addiction to masturbation and child pornography. They find children attractive and vulnerable, thus enabling them to abuse and overpower these children. The findings also indicate that the victims are badly affected by the acts more so for those who have been abused by their own fathers. It is found that the boys tend to show aggressive behavior while the girls tend to feel scared and choose to be in isolation. The widely used treatment of cognitivebehavior therapy is not as effective in treating the predators and victims. Art therapy has been found to be very effective in helping children draw out their trauma. The Sexual Offences against Children Bill 2017 passed recently is a new law protecting children from sexual abuse and crimes in line with the Child Act 2001.